Development of agency as semiotic empowerment : A Peircean analysis - Ojala, Juha (Mouton De Gruyter, 2023)
The chapter provides a naturalist-pragmatist analysis of agency and its development across the continuum of biological and social processes of signification using Peircean tools such as phaneroscopic categories, semiotic triangle, the tenfold Sign, as well as inquiry, habits, representation, and hard and soft facts. The sensorimotor agent is a simple semiotic system: an organism with “direct coupling” with the environment. The embodied basis of its learning enables the development of agency. Meaning is located in habits of action, as habits allow for the prediction of future. Through hard and soft facts, we negotiate our position in the world. For that, inquiry involves constant evaluation of the relation of the Signs of ourselves and other Objects, including other subjects. The communicative revelation empowers the instrumental agent to claim the semiotic space of opportunities to operate with signs for self and for others to interpret, reaching the full extent of semiotic agency.
Keywords: semiotiikka; musiikkisemiotiikka; oppiminen; musiikki; identiteetti; musiikkifilosofia